Studi Identifikasi Potensi Pariwisata & Kuliner Kabupaten Indramayu, Provinsi Jawa Barat - Chandra, Teddy (Jurnal Master Pariwisata (JUMPA), 2022)
“The Identification study of Tourism and cullinary at the Indramayu Regency, West Java Province” is the research which has purpose to identified about the tourism and cullinary potentiality at the Indramayu Regency, West Java Province. The research question of this research is: 1) how is the actual condition of the Indramayu Regency as a tourism destination?, 2) how is the actual condition of the tourism site at the Indramayu Regency as a tourism destination?, 3) how is the actual condition of the local cullinary at the Indramayu Regency as a tourism destination? This research is done by the qualitative method. The data was collected  by: 1) literature study, 2) observation and 3) interview. The result of the research shown that Indramayu Regency has several potential tourism site and local potential cullinary to become a tourism atraction and destination. Keywords: tourism, cullinary, indramayu, west java.